On Two-Ridge Structure in Two-Particle Azimuthal Correlations in Proton-Lead Collisions at Large Hadron Collider Energy - Fu-Hu Liu; Tian Tian; Ya-Qin Gao (Advances in High Energy Physics)
Two-particle azimuthal correlations are studied in the framework of a multisource thermal model. Each source is assumed to produce many particles. Each particle pair measured in final state is considered to be produced at two emission points (subsources) in a single or two sources. The first emission point corresponds to the production of “trigger” particle and the second one corresponds to that of “associated” particle. There are oscillations and other interactions between the two emission points. In the rest frame of the “associated” particle's emission point, the oscillations and other interactions cause the momentum of the “trigger” particle to depart from the original value. The modelling results are in agreement with the experimental data of proton-lead (p-Pb) collisions at sNN = 5.02 TeV, one of the Large Hadron Collider energies, measured by the ALICE and ATLAS Collaborations.